Introduction to scanning tunneling microscopy - Chen, C. Julian (Oxford University Press, 2021)
The scanning tunnelling microscope (STM) was invented by Binnig and Rohrer and received a Nobel Prize of Physics in 1986. Together with the atomic force microscope (AFM), it provides non-destructive atomic and subatomic resolution on surfaces. Especially, in recent years, internal details of atomic and molecular wavefunctions are observed and mapped with negligible disturbance. This is a reference book on the topic.
This edition also issued in print: 2021.
Keywords: Scanning tunneling microscopy.; elektronické knihy; electronic books